The possibility of using stevia in the development of therapeutic and prophylactic food. (Experimental biology, 2015)
The article presents data on the possibility of the development of new therapeutic and prophylactic products for dairy and bakery basics, as well as dietary supplements with the addition of stevia.
Keywords: Stevia sweetener; medical and preventive food development